And what can context do for data? - Bolchini, C; Curino, C; Orsi, G; Quintarelli, E; Rossato, R; Schreiber, F; Tanca, L (2009)
Common to all actors in today’s information world is the problem of lowering the “information noise”, both reducing the amount of data to be stored and accessed, and enhancing the “precision” according to which the available data fit the application requirements. Thus, fitting data to the application needs is tantamount to fitting a dress to a person, and will be referred to as data tailoring. The context will be our scissors to tailor data, possibly assembled and integrated from many data sources.